2006
DOI: 10.1002/da.20162
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal behavioral similarity between patients with depression in remission and interviewers in relation to satisfaction and recurrence of depression

Abstract: Unsatisfying interpersonal relationships are involved in the onset and course of depression. However, little is known about the underlying mechanisms. In this study we investigated the nonverbal communication between 101 patients with remitted depression and interviewers. We related the interaction between the patients' and interviewers' behavior to patients' satisfaction with the interview and to the risk of recurrence of depression. We registered the patients' and interviewers' nonverbal displays of involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…It is conceivable that in more severe cases of psychopathology (e.g. severe major depressive episode/acute mania), synchrony could be less evident (Geerts et al, 2006) when nonverbal behavior is more strongly influenced by psychopathology (Kupper et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that in more severe cases of psychopathology (e.g. severe major depressive episode/acute mania), synchrony could be less evident (Geerts et al, 2006) when nonverbal behavior is more strongly influenced by psychopathology (Kupper et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A large percentage of the remaining studies relied on cross-correlations (N = 11), which typically quantified coordination by taking an absolute value of the cross-correlation functions across windows and at various lags (e.g., Galbusera et al 2016;Ramseyer and Tschacher 2011). In addition, there were a number of studies that used various scores (N = 15) that involved calculating differences between speaking efforts (Geerts et al 2006) or skin conductance levels (Marci et al 2004), summing dominant behaviors of the patient and therapist (Altenstein et al 2013), or dividing complementary behaviors of the patient by those of the therapist (Ahmed et al 2012). Three studies used cross-recurrence quantification analysis.…”
Section: Methods Summarymentioning
confidence: 99%
“…In depression, it has been demonstrated that the analysis of nonverbal behavior may have greater predictive value in terms of response to treatment and relapse than standard rating scales for psychopathology (Bouhuys, 2003;Fossi et al, 1984;Geerts et al, 1996;McGuire and Polsky, 1979;Schelde et al, 1988;Schelde, 1994Schelde, , 1998Troisi et al, 1989). Specifically, Geerts et al (1995Geerts et al ( , 1996 revealed that the degree of convergence of nonverbal behaviors between patient and therapist during an interview predicts outcome and treatment response (Geerts et al, 2006). Therefore, these studies clearly underscore the usefulness of ethological approaches for several clinically relevant issues, including prediction of relapse, response to treatment, and recovery (reviewed in Geerts and Brüne, 2009).…”
mentioning
confidence: 96%